2019
DOI: 10.3847/1538-4357/ab141a
|View full text |Cite
|
Sign up to set email alerts
|

Open and Closed Magnetic Configurations of Twisted Flux Tubes

Abstract: We construct two classes of magnetohydrostatic (MHS) equilibria for an axisymmetric vertical flux tube spanning from the photosphere to the lower part of the transition region within a realistic stratified solar atmosphere subject to solar gravity. We assume a general quadratic expression of the magnetic flux function for the gas pressure and poloidal current and solve the Grad-Shafranov equation analytically. The solution is a combination of a homogeneous and a particular part where the former is separable by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…coronal holes (CHs), coronal bright points, plumes, interplumes, moss regions) has been calculated in past (Warren et al 2008;Tripathi et al 2010;Hahn & Savin 2016). These regions are the open magnetic structures, where the magnetic field lines rise but never come back in the same horizontal plane within the region of interest (Sen & Mangalam 2019). Dere (2008) has estimated the filling factor of the coronal bright points in the quiet Sun (QS) regions by EUV Imaging Spectrometer (EIS) onboard Hinode (Culhane et al 2007) data, and found it to vary from 4 × 10 −5 to 0.20 with a median value of 0.015.…”
Section: Introductionmentioning
confidence: 99%
“…coronal holes (CHs), coronal bright points, plumes, interplumes, moss regions) has been calculated in past (Warren et al 2008;Tripathi et al 2010;Hahn & Savin 2016). These regions are the open magnetic structures, where the magnetic field lines rise but never come back in the same horizontal plane within the region of interest (Sen & Mangalam 2019). Dere (2008) has estimated the filling factor of the coronal bright points in the quiet Sun (QS) regions by EUV Imaging Spectrometer (EIS) onboard Hinode (Culhane et al 2007) data, and found it to vary from 4 × 10 −5 to 0.20 with a median value of 0.015.…”
Section: Introductionmentioning
confidence: 99%